Recent advances on 3D-printed PCL-based composite scaffolds for bone tissue engineering - Gharibshahian, Maliheh; Salehi, Majid; Beheshtizadeh, Nima; Kamalabadi-Farahani, Mohammad; Atashi, Amir; Nourbakhsh, Mohammad-Sadegh; Alizadeh, Morteza (Frontiers in Bioengineering and Biotechnology, 2023)
Population ageing and various diseases have increased the demand for bone grafts in recent decades. Bone tissue engineering (BTE) using a three-dimensional (3D) scaffold helps to create a suitable microenvironment for cell proliferation and regeneration of damaged tissues or organs. The 3D printing technique is a beneficial tool in BTE scaffold fabrication with appropriate features such as spatial control of microarchitecture and scaffold composition, high efficiency, and high precision. Various biomaterials could be used in BTE applications. PCL, as a thermoplastic and linear aliphatic polyester, is one of the most widely used polymers in bone scaffold fabrication. High biocompatibility, low cost, easy processing, non-carcinogenicity, low immunogenicity, and a slow degradation rate make this semi-crystalline polymer suitable for use in load-bearing bones. Combining PCL with other biomaterials, drugs, growth factors, and cells has improved its properties and helped heal bone lesions. The integration of PCL composites with the new 3D printing method has made it a promising approach for the effective treatment of bone injuries. The purpose of this review is give a comprehensive overview of the role of printed PCL composite scaffolds in bone repair and the path ahead to enter the clinic. This study will investigate the types of 3D printing methods for making PCL composites and the optimal compounds for making PCL composites to accelerate bone healing.